Cultura Política - Revista Mensal de Estudos Brasileiros (1941 a 1945): um voo panorâmico sobre o ideário político do Estado Novo - Câmara, Marcelo Barbosa (2010)
This project was based on research of the publication Cultura Política Revista Mensal de Estudos Brasileiros published by the Department of Press and Propaganda (DIP) from 1941 to 1945 and directed by Almir Andrade. Based on the texts of the employees of the magazine, we sought to build a picture of what we understand as being the ideological frameworks of the New State (Estado Novo), the political regime established in Brazil in 1937 that would last until 1945. The texts are divided into 4 chapters, the first deals with the political thought of the period with an emphasis on the relationship between intellectuals and power. These authors became known as ―authoritarian thinking intellectuals‖ along with others who reflected on that period and other issues pertaining to politics of the time. The second chapter describes how the magazine was structured, in terms of its editorial layout and design. It also describes their existence as a magazine produced by the State, and details the profile of its employees. The third chapter is devoted to the construction of what we call the 37 s Reasons (Razões de 37). These reasons originated from the issues that gave rise to the shift that occurred in the 30 s Revolution, especially with the 1937 regime. The analysis of the ―37 s Reasons‖ was done by studying the collaborations of the authors who wrote in the journal Cultura Política. The fourth chapter deals with the perception that the magazine and its employees had about the construction of the new company that would be erected by the New State as well as the reactions that the authors had about the solutions given by the scheme, particularly the 37 s Constitution. It also addresses the criticism of the regime and the author s responses to critiques that may be viewed in the magazine. Lastly we analyze the new phase, an initiative by the editor that was marked by the last three publications of the magazine which now have no connection with the DIP. We believe that the study of authoritarian political thought and especially of the Cultura Política Revista Mensal de Estudos Brasileiros, serve as a base for understanding the political actions of the New State as well as deepening the understanding of that historical period